CONTINUOUS HYDROLYSIS OF OLIVE OIL USING INDIGENOUSLY DEVELOPED IMMOBILIZED LIPASE WITH HIGHER EFFICIENCY - SOUMASREE TAPADAR; Dr.SOHAM CHATTOPADHYAY (International Journal of Pharma and Bio Sciences, 2016)
Lipase producing bacteria was isolated and screened from waste water near east Kolkata waterbodies (West Bengal). After screening, the media showed maximum lipase activity were selected for furter studies. The Maximum specific activity of lipase was calculated as 2.44 mg/min.mg protein for selected media. Qualitative and quantitative estimation of lipase confirmed the presence of lipase in the fractions obtained from 60% to 70% ammonium sulphate cut offs. Hydrolysis of olive oil was enhanced with increasing water concentration and maximum free fatty acid was obtained in 0.13% of water (v/v of oil). Purified lipase was immobilized in different matrices and egg shell immobilized lipase was found to be best in terms of its hydrolysis efficiency. Continuous process with immobilized lipase indicated that it was stable for 216 min with better hydrolysis efficiency as compared to batch process. The present study provides a benchmark for indigenously developed immobilized lipase system for different applications.